Relaxation Therapy to Decrease Anxiety Level in Eldely: A Literature Review - Lestari, Gangsar Indah; Priyono, Djoko; Putri, Triyana Harlia (Tanjungpura Journal of Nursing Practice and Education, 2021)
The aging process results in psychosocial in elderly. Anxiety is a psychosocial problem that often experienced by elderly but gets less attention than depression and stress problems. Anxiety is caused by internal and external factors. Symptoms of anxiety in elderly are characterized as fear, worry, anxiety and panic. Anxiety can be overcome with relaxation therapy, but there is no known the most effective relaxation to decrease anxiety level in the elderly. Therefore a literature review is needed to do. Objective : Finding the most effective relaxation therapy to decrease anxiety level in elderly. Methode : Research use electronic database that consist of Pubmed,Science Direct, Google Schoolar and according to inclusion criteria. Result : Seven articles show that relaxation therapies can decrease anxiety level in elderly and the most effective relaxation therapy showed by laugh therapy. Keyword : relaxation, anxiety and elderly.